2021
DOI: 10.1186/s12879-021-06326-x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Escherichia coli bloodstream infections: a multinational population-based cohort study

Abstract: Background Escherichia coli is the most common cause of bloodstream infections (BSIs) and mortality is an important aspect of burden of disease. Using a multinational population-based cohort of E. coli BSIs, our objectives were to evaluate 30-day case fatality risk and mortality rate, and determine factors associated with each. Methods During 2014–2018, we identified 30-day deaths from all incident E. coli BSIs from surveillance nationally in Finla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The survival analysis of our study of the hospital mortality rate showed that the hospital E. coli bacteremia mortality was lower than bacteremia due to other strains. This follows a recent review where the case fatality rate for in-hospital E. coli bacteremia did not differ appreciably from that in the general population [30].…”
Section: Resultssupporting
confidence: 75%
“…The survival analysis of our study of the hospital mortality rate showed that the hospital E. coli bacteremia mortality was lower than bacteremia due to other strains. This follows a recent review where the case fatality rate for in-hospital E. coli bacteremia did not differ appreciably from that in the general population [30].…”
Section: Resultssupporting
confidence: 75%
“…In our study the overall mortality of Achromobacter BSI was 20% by day-90, rising to 27% in patients with 3 or more comorbidities as denoted on the Charlson Comorbidity Index. This is as high as the mortality rates for the BSIs caused by more commonly encountered pathogens, hence would warrant more attention [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Diarrhea cause by antibiotic-resistant pathogens can lead to severe illnesses, extended hospital stays, increase in healthcare costs, socio-economic burden as well as treatment failures (Rahim et al, 2021). The death rate in humans resulting from complications caused by resistant Diarrheagenic bacteria has increased globally (Vos et al, 2020;Mac Kinnon et al, 2021). In 2019, the global death caused by notable Diarrheagenic bacteria such as E. coli, V. cholerae, Shigella, Salmonella, Campylobacter, and Clostridium species were 60,414, 117,240, 148,202, 61,646, 139,079, and 32,134, respectively (IHME, 2020).…”
Section: Diarrhea Therapy and Antibiotics Resistance Crisismentioning
confidence: 99%